The "Organic" Descriptor and Its Association With Commercial Cigarette Health Risk Expectancies, Subjective Effects, and Smoking Topography: A Pilot Human Laboratory Study. Issue 1 (21st July 2021) - Pearson, Jennifer L; Watanabe, Mika; Sanchez, Jennifer; Mann, Suman; Drake, Cara; Mercincavage, Melissa
Abstract: Introduction: The purpose of this mixed-method pilot study was to: (1) examine whether the "organic" descriptor affects smokers' health risk expectancies, subjective ratings of smoking, and topography, and (2) describe how smokers interpret the "organic" descriptor and relate it to their subjective smoking experience. Methods: Twenty-two daily smokers (45.5% men, 81.8% non-Hispanic White, M (SD) age = 47.3 [12.7], M (SD) cigarettes/day = 14.5 [5.1]) completed a within-person laboratory study. Following a baseline session, smokers attended 2 experimental sessions where they smoked a study-provided cigarette (identical across conditions) paired with either an "organic" or conventional (e.g., no "organic") descriptor condition and completed subjective and behavioral measures. Participants completed a semi-structured interview at the last visit. Results: Relative to the conventional cigarette, more participants rated the "organic" cigarette as healthier, having fewer chemicals, and having a more favorable burn rate ( P 's < 0.05). There were no differences in total puff volume by condition ( P = 0.42). Stratifying by gender, men inhaled 225 ml (SE = 82.7) more in the conventional condition ( P = 0.02); women inhaled 408 ml (SE = 233.3) more in the organic condition ( P = 0.11). A common understanding of "organic" was that the product was "…less processed... like less chemicals and it's more natural." Some believed that "organic" cigarettes contained fewer chemicals, which in turn produced a "much cleaner and healthier smoking cigarette" and that they could "taste the difference." Conclusions: Findings support that smokers associate the "organic" descriptor with health and reduced harm. This descriptor may differentially impact puffing behavior by gender. Implications: This study provides qualitative and quantitative data regarding how the "organic" descriptor influences adult daily smokers' perceptions and use of cigarettes. After smoking two identical cigarettes described as "organic" and conventional (e.g., no "organic"), smokers expressed more problematic health expectancies about the "organic" cigarette condition, providing further empirical support that the "organic" descriptor is associated with expectancies of reduced harm. The source of reduced harm was understood to be fewer chemicals in the organic cigarette. Though preliminary, findings suggest that "organic" may differentially affect puffing behavior by gender.